2018
DOI: 10.1016/j.cels.2018.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Rare Cell Detection by Single-Cell RNA Sequencing as Guided by Single-Molecule RNA FISH

Abstract: Although single-cell RNA sequencing can reliably detect large-scale transcriptional programs, it is unclear whether it accurately captures the behavior of individual genes, especially those that express only in rare cells. Here, we use single-molecule RNA fluorescence in situ hybridization as a gold standard to assess trade-offs in single-cell RNA-sequencing data for detecting rare cell expression variability. We quantified the gene expression distribution for 26 genes that range from ubiquitous to rarely expr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
145
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
2

Relationship

2
8

Authors

Journals

citations
Cited by 126 publications
(154 citation statements)
references
References 27 publications
8
145
0
1
Order By: Relevance
“…Before normalization, a series of filtering steps was performed. Only those cells showing at least 1,500 detected genes and 5,000 UMIs were considered for further analyses (Torre et al, 2018). Reads mapping on mitochondrial genes were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Before normalization, a series of filtering steps was performed. Only those cells showing at least 1,500 detected genes and 5,000 UMIs were considered for further analyses (Torre et al, 2018). Reads mapping on mitochondrial genes were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…Therapies such as vemurafenib designed to inhibit particular oncogenic targets can often kill most of the tumor cells, but a few remaining cells can continue to proliferate, ultimately repopulating the tumor. While the mechanisms underlying this therapy resistance can sometimes be the result of a genetic mutation, many recent studies, both in melanoma and other cancers, suggest that cellular plasticity may also dictate which cells are able to survive drug treatment, with rare primed cells being reprogrammed by the addition of drug into a stably resistant state 8,[11][12][13][14][15][16][17][18][19][20][21] . In melanoma, this rare primed cellular state, which we have also previously referred to as the pre-resistant cellular state, is often marked by transiently high expression of several resistance marker genes, such as EGFR , NGFR and AXL (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…This equation predicted that over a relatively large range of reasonable parameters, (CV ~ 0.5-2, fraction of time on ~ 0.01), the predicted memory was mostly in the range of 5-10 divisions, matching our experimental observations. Motivated by our previous work in this cell line, we also looked for correspondences between the degree of heritability and the rarity of gene expression as measured by the Gini coefficient, a metric for inequality (Jiang et al, 2016;Shaffer et al, 2017;Torre et al, 2018) . We observed that indeed the two metrics were correlated (adjusted R 2 = 0.4898) ( Fig.…”
mentioning
confidence: 99%